2011
DOI: 10.1039/c1cp21028a
|View full text |Cite
|
Sign up to set email alerts
|

Complex kinetics and significant influences of bromine removal in ferroin–bromate–metol reaction

Abstract: This study presents a new bromate-based chemical oscillator that employs metol as the organic substrate. Complex reaction behaviors were observed when the system was subjected to bromine removal and oxygen exposure. Transitions from simple to sequential oscillations took place as a function of the age of the metol stock solution. MS spectroscopy measurements and parallel kinetic experiments with a mixture of metol and hydroquinone suggest that the decomposition of metol to hydroquinone was responsible for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…On the other hand, the importance of bromide ions in chemical and electrochemical oscillations is well documented [5][6][7][8][9][10]. For example, oscillations have been observed during the electro-dissolution of gold in an electrolyte solution containing bromide ions [9].…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, the importance of bromide ions in chemical and electrochemical oscillations is well documented [5][6][7][8][9][10]. For example, oscillations have been observed during the electro-dissolution of gold in an electrolyte solution containing bromide ions [9].…”
Section: Introductionmentioning
confidence: 98%
“…The reaction behavior of several uncatalyzed bromate oscillators including the bromate–phenol system has been reported to exhibit great dependence on stirring. ,, Such a dependence may arise from its influences on the extremely fast reaction steps or the influence on the diffusion of volatile species as well as oxygen out/into the reaction solution. It has previously been shown that oxygen can increase the induction period as well as gradually decrease the amplitude of the oscillatory behavior in the BZ oscillator. , To shed light on the effects of oxygen on this reaction, the reaction solution was first purged with nitrogen gas to remove any excess oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…29 Our earlier study has shown that bromine removal could have significant impact on the behavior of modified BZ reactions. 30 To examine whether the escape of volatile species played a key factor in causing the oscillatory behavior in the above reaction, we have run parallel experiments by flowing nitrogen or air above the reaction solution surface. Figure 2 presents the results achieved under the flow of air at 60 mL/ min.…”
Section: Resultsmentioning
confidence: 99%